Workplace Safety and Efficiency in Laboratories: A Comprehensive Review - Alahmdi, Razan Abdullah; Alkhawaher, Wujood Hussain; Bakri, Reham Emad; Aljohani, Kawther Salah; Alguhtani, Yara Ahmed; Alzahrani, Yousef Ahmed Abdullah; Alqarni, Dareen Abdullah; Bukhari, Shayraman Abdulrashid; Alharbi, Huda Mohammed; Alamri, Mousa Mikhdhar; Gezani, Hadeel Omar; Fallatah, Amal Abdulrahman; et al. (Journal of Posthumanism, 2024)
This comprehensive review examines the critical relationship between workplace safety and operational efficiency in modern laboratory environments. The paper explores essential safety components, including hazard assessment, personal protective equipment, engineering controls, biological and chemical risk management, ergonomics, fire and electrical safety, and waste management. It further analyzes workflow optimization strategies such as automation, digitalization, inventory control, communication, and continuous quality improvement. The review highlights how emerging technologies—such as robotics, artificial intelligence, and data-driven systems—are reshaping laboratory safety protocols and efficiency outcomes. Additionally, it emphasizes the ethical, regulatory, and quality-control frameworks required to maintain scientific integrity. By integrating safety culture with innovation, laboratories can achieve improved productivity, reduced incident rates, and sustained operational excellence. This paper provides a holistic foundation for strengthening laboratory practices in clinical, research, and industrial settings